Case Report: Abruptio placentae and epileptic seizure after occurrence of perinatal hyperglycaemia in woman with gestational diabetes mellitus and hypertriglyceridemia-induced acute pancreatitis - He, Yanlang; Huang, Zhijie; Wei, Changli; Chen, Jianyong (Frontiers in Endocrinology, 2023)
Hypertriglyceridemia-induced acute pancreatitis seldom occurs in the second trimester of pregnancy with gestational diabetes mellitus. For these patients, the existing knowledge on concomitant hyperglycemia is not sufficient. We report a case of abruptio placentae and epileptic seizure following perinatal hyperglycaemia in woman with gestational diabetes mellitus and hypertriglyceridemia-induced acute pancreatitis. The occurrence of abruptio placentae and epileptic seizure may be associated with concomitant hyperglycemia, and the epileptic seizure was terminated after she underwent treatment with insulin. We should pay more attention to the adverse effects of perinatal hyperglycemia and continue to give appropriate insulin treatment even if patients have passed the acute phase of hypertriglyceridemia-induced acute pancreatitis.Pregnant women with gestational diabetes mellitus(GDM) usually return to normal blood glucose after delivery due to reduced insulin resistance 1-2 . As a result, the effects and management of perinatal hyperglycemia, especially in women with acute pancreatic disease, have been poorly studied. In addition, hypertriglyceridemia-induced acute pancreatitis (HTG AP) rarely occurs in the second trimester of pregnancy [3][4][5] . Here, we describe a rare case of abruptio placenta and epileptic seizure following perinatal hyperglycaemia in woman with GDM and HTG AP in the second trimester, discuss possible causes, and compare treatment options for concomitant hyperglycaemia in the perinatal period.